CD44 on cancer stem cell is a potential immunological and prognostic pan-cancer biomarker - Ya-Juan Zhu; Si-Ying Li; Shan-Shan Yang; Yang Du; Zhuo-Yuan Zhang; Ji-Yan Liu (Cancer Cell International)
Abstract Background CD44, a widely recognized cancer stem cell marker, displayed a vital participation in the cancer immune invasion and may related with the response to the immunotherapy. However, the role of CD44 in cancer immunology is not well defined. Therefore, we intended to explore its prognostic value and potential immunological functions across 33 human cancer types. Methods Based on the data of patients from The Cancer Genome Atlas (TCGA), Sangerbox was used to analyze the correlations between CD44 expression and tumor-infiltrated immune cells, immune checkpoints, neoantigens, microsatellite instability (MSI), and tumor mutational burden (TMB) in human cancers. A mouse model xenografted with shRNA-CD44 MC38 was established. Results The elevated CD44 was associated with tumor stage and prognosis in several different cancers. GSEA results showed that upregulated CD44 involved in cancer stem cell associated process, antigen processing and presentation, and immune cells proliferation and activation. CD44 plays an essential role in the tumor immune regulation and immune checkpoints inhibitor response. The correlation of CD44 gene expression and infiltration levels of immune cells varied across different cancer types. Notably, the upregulation of CD44 expression is positively correlated with regulatory CD4 T cells, macrophages M1 and M2 in several analyzed cancers. Furthermore, we verified the effect of CD44 on tumor growth and immune microenvironment in mouse xenografted with shRNA-CD44 MC38. Moreover, DNA methylation existed in CD44 expression and associated with dysfunctional T-cell phenotypes via different mechanisms, thus resulting in tissue-dependent prognoses. Conclusion CD44 is both a cancer stem cell marker and a potential prognostic and immunological biomarker in various malignant tumors. Moreover, CD44 could be a novel target for immune-based therapy.